Notes on the tribe Nygmiini (Lepidoptera: Erebidae: Lymantriinae) from Nanling National Nature Reserve, with description of a new species - Wang, Houshuai; Wang, Min; Fan, Xiaoling (Zootaxa, 2011)
Thirteen species belonging to seven genera of the tribe Nygmiini are recognized from Nanling National Nature Reserve, Guangdong province, China. A new species, Arna bicostata sp. nov., is described, and two species are transferred as new combinations: Artaxa angulata comb. nov. and Toxoproctis croceola comb. nov.. Adults and their genitalia are illustrated.